TERAPI MUSIK KLASIK MENURUNKAN STRES MAHASISWA KEPERAWATAN TINGKAT AKHIR - Riyadi, Muskhab Eko; Laily, Suha; Kusumasari, Viantika (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
Stress that occurs in students is usually called academic stress. Stress is often experienced by students because of the many demands in the academic field. A national study of 200,000 students at more than 400 tertiary institutions, states that the incidence of academic stress and depression in students is greater than ever before. Student academic stress can be treated with music therapy, it is stated that music therapy can be used as a medium to reduce academic stress levels in students. This study aims to determine the effect of classical music therapy on the stress level of final year nursing students. This is a pre experimental study, with a one-group pre test post test design, in which the researcher measures the stress level of students first, after which they are given classical music therapy treatment, which is then measured by the respondent's stress level after the treatment using the Perceived measuring instrument. Stress Scale PSS. The population in this study were all final year nursing students at STIKes Surya Global Yogyakarta, namely a total of 152 students. The sample size in this study was 31 respondents. The sampling technique uses a simple random sampling technique. While the statistical test used the Wilcoxon test. The results showed that the stress level of students before treatment was severe stress, then after being given treatment the stress level was included in the moderate stress category. The p value is 0.000, which means that classical music therapy has a significant effect on reducing the stress level of final year nursing students.